LAS ENCUESTAS DE OPINIÓN PÚBLICA - Kavanagh, Dennis (La Sociología en sus Escenarios, 2012)
Abstract. In this paper is analyzed, the role and impact of the surveys of public opinion in the electoral processes and is examined, the paper of the soundings realized by private institutions, supposedly independent. The most frequent repairs of those than the electoral surveys are object and, finally, the meaning is evaluated that these have in the elections in the contemporary democracies. According to the reviewed studies and information, the author indicates that the surveys constitute an important instrument of manipulation in the political activity. In relation to the possible distorting influence on the vote that could exert the soundings, or its diffusion in date near the elections, is indicated that it is evident that the electorate alters his intention of vote based on the results of the partial surveys. Finally, the author emphasizes that the existence of a plurality of surveys, realized by different institutions, does not act as to neutralize the always latent danger on attempts of manipulation through collected or the interested filtration of the data to the media. Resumen. En este artículo se analiza, el rol e impacto de las encuestas de opinión pública en los procesos electorales y se examinan, el papel de las sondeos realizados por organismos privados, supuestamente independientes, los reparos más frecuentes de los que son objeto las encuestas electorales y, finalmente, se evalúa la significación que éstas tienen en las elecciones en las democracias contemporáneas. De acuerdo a los estudios e información revisados, el autor señala que las encuestas constituyen un importante instrumento de manipulación en la actividad política. En relación a la posible influencia deformadora sobre el voto que podrían ejercer los sondeos, o su difusión en fecha cercana a las elecciones, se señala que es evidente de que el electorado altera su intención de voto en función de los resultados de las encuestas parciales. Por último, el autor subraya que la existencia de una pluralidad de encuestas, realizadas por distintas instituciones, no cumple la función de neutralizar el peligro siempre latente de intentos de manipulación a través de la información recogida o de la filtración interesada de los datos.